Relationship between inosine triphosphate genotype and outcome of extended therapy in hepatitis C virus patients with a late viral response to pegylated‐interferon and ribavirin. Issue 1 (January 2014) - Hai, Hoang; Tamori, Akihiro; Enomoto, Masaru; Morikawa, Hiroyasu; Uchida‐Kobayashi, Sawako; Fujii, Hideki; Hagihara, Atsushi; Kawamura, Etsushi; Thuy, Le Thi Thanh; Tanaka, Yasuhito; Kawada, Norifumi
Abstract Background and Aim It is not yet clear which factors are associated with the outcome of 72‐week treatment with pegylated‐interferon and ribavirin (RBV) in patients with chronic hepatitis C virus (HCV) infection. Methods In 66 patients with HCV genotype 1 who had a late viral response (LVR) to 72‐week treatment of pegylated‐interferon and RBV, we examined the factors that determined the outcome, including single nucleotide polymorphisms of interleukin‐28B and inosine triphosphatase (ITPA) genes. Results Thirty seven of 66 (56%) patients with LVR achieved a sustained viral response (SVR). The mean age of these 37 SVR patients was 55, compared with 61 in 29 relapsed patients (P = 0.009). Twenty six of 54 (48%) patients with the CC genotype and 11 of 12 (92%) with the CA/AA genotype of ITPA rs1127354 achieved SVR (P = 0.006). The SVR rates were 79%, 40%, 60%, and 33% in patients with undetectable HCV RNA on weeks 16, 20, 24, and 28 or later, respectively (P = 0.014). Finally, serum RBV concentration at week 44 of treatment was significantly higher in the SVR group (2651 ng/mL) than in the relapse group (1989 ng/mL, P = 0.002). In contrast, the rate of the interleukin‐28B genotype was not different between the groups. Multiple regression analysis showed that age < 60 years, ITPA CA/AA genotype, and serum RBV concentration were significant independent predictive factors for SVR. Conclusions Our findings elucidated the association of four factors, including ITPA genotype, with the outcome of 72‐week treatment in LVR patients.